A Pilin Region Affecting Host Range of the Pseudomonas aeruginosa RNA Phage, PP7 - Kim, Eun Sook; Bae, Hee-Won; Cho, You-Hee (Frontiers in Microbiology, 2018)
The host range of a phage is determined primarily by phage-receptor interaction. Here, we profiled the host range of an RNA leviphage, PP7 that requires functional type IV pilus (TFP) in order to enter into its host bacterium, Pseudomonas aeruginosa. Out of 25 twitching-proficient P. aeruginosa strains, 4 with group I pilin and 7 with group III pilin displayed PP7-resistance. The remaining 14 possessed group II pilin, which included 10 PP7-sensitive and 4 PP7-resistant strains, suggesting that only the strains with TFP consisted of a subset of group II (hence, group IIa) pilin were susceptible to PP7. The co-expression of the PAO1 (group IIa) pilin rendered all the strains susceptible to PP7, with the exception of the 4 strains with group I pilin. Moreover, the expression of PA14 (group III) and PAK (group IIb) pilin in the PAO1 pilA mutant restored the twitching motility but not the PP7-suceptibility. Site-directed and random mutation analyses of PAO1 pilin enabled us to identify a pilin mutant (G96S) that is fully functional but resistant to PP7 infection. This is due to the lack of any phage-receptor interactions, suggesting the structural properties of the β1-β2 loop in the variable region 2 of the group II pilin might be involved in PP7 infection.